Local scour of cohesive sediment bed at the pile subjected to lateral vibration. (1st December 2022) - Zhang, Minxi; Sun, Hui; Yao, WenJuan; Yu, Guoliang
Abstract: In this study, the local scour of cohesive sediment bed at the pile subjected to lateral vibration was investigated experimentally. The experiments were carried out in a unidirectional free-surface flow channel in the laboratory. The findings of the experiments indicate that lateral vibrations produce significant effects on local scour of the bed at the pile, and the effects are completely different for non-cohesive and cohesive sediment bed. For non-cohesive sediments, the equilibrium scour depth decreases with the increase of vibration intensity. On the contrary, for cohesive sediments, the equilibrium scour depth increases with the increase of vibration intensity, and there appears a peak and plateau, which may be attributed to the shear-thinning behavior of cohesive sediments near the pile under vibration loadings. Cohesive sediments around the pile are fluidized by vibration, so that the cohesive force among sediment particles decreases, resulting in larger local scour. An empirical formula for estimating equilibrium local scour depth at pile foundation subjected to lateral vibration is proposed and tested using reported data and data obtained in this study. Highlights: Lateral vibrations produce significant effects on local scour of the bed at the pile. The effects of vibrations are different for cohesive and non-cohesive sediment bed. For cohesive sediments, the equilibrium scour depth increases with vibration intensity. The larger local scour may be attributed to the fluidization of sediments induced by vibration. An empirical formula was proposed to estimate the local scour at a vibrating pile.